Critical theories connecting gapped phases with ℤ 2 × ℤ 2 symmetry from the duality web - Andreas Karch; Ryan C. Spieler (Journal of High Energy Physics)
Abstract We use the ideas behind the duality web to construct numerous conformal field theories mediating the phase transitions between various symmetry broken and topological phases. In particular we obtain the full field theory version of the Kennedy Tasaki transformation, mapping a gapless theory mediating a topological phase transition of symmetry protected topological orders to a standard symmetry breaking one in a 1+1 dimensional ℤ 2 × ℤ 2 gauge theory. When we consider all possible discrete gauging operations, we obtain bosonic and fermionic webs with 9 critical theories per web, each connecting 4 separate gapped phases, some of them topological. Bosonization maps the two webs into each other. In addition to discussing the multi-critical theory connecting the four gapped phases in each phase diagram, we discuss the partially gapped theories connecting two of those four. Some of these are gapless symmetry protected topological phases.